2015
DOI: 10.1002/adfm.201404629
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Polymer Modified Mesoporous Silica Nanoparticles for Targeted siRNA Delivery to HER2+ Breast Cancer

Abstract: In vivo delivery of siRNAs designed to inhibit genes important in cancer and other diseases continues to be an important biomedical goal. We now describe a new nanoparticle construct that has been engineered for efficient delivery of siRNA to tumors. The construct is comprised of a 47-nm mesoporous silica nanoparticle (MSNP) core coated with a cross-linked PEI-PEG copolymer, carrying siRNA against the HER2 oncogene, and coupled to the anti-HER2 monoclonal antibody (trastuzumab). The construct has been engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
195
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(203 citation statements)
references
References 81 publications
(57 reference statements)
5
195
0
Order By: Relevance
“…Enzymatic degradation, removal from circulation by renal excretion or mononuclear phagocyte system (MPS), poor cellular uptake and endosomal release are examples of physiological barriers that siRNAs need to overcome [17,18]. Several viral and nonviral delivery vectors, such as adenovirus, polyplexes, liposomes, and micelles, amongst others, have been developed to overcome these obstacles and improve RNAi therapeutic efficacy in vivo [19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…Enzymatic degradation, removal from circulation by renal excretion or mononuclear phagocyte system (MPS), poor cellular uptake and endosomal release are examples of physiological barriers that siRNAs need to overcome [17,18]. Several viral and nonviral delivery vectors, such as adenovirus, polyplexes, liposomes, and micelles, amongst others, have been developed to overcome these obstacles and improve RNAi therapeutic efficacy in vivo [19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…The MSN@PEI@oligonucleotide multilayer deposition strategy has been also reported for the construction of targeted, gene silencing nanodevices employing the sense: 5'-(CAC GUU UGA GUC 144 The authors demonstrated in vitro and in vivo that the system so designed was successfully taken up by HER2 positive cells, in which was produced the expected gene silencing and the restoration drug sensitivity. Furthermore, this siRNA delivery induced apoptotic death of HER2 positive while the negative cells remained unaffected, opening the way to the construction of synergistic therapy nanodevices (Section 4.3).…”
Section: Surface Deposition Of Nucleic Acids Onto Msns For Gene Transmentioning
confidence: 99%
“…The polydispersity index (PDI) of F10 (about 0.28) suggests a relatively narrow size distribution. Generally, PDI < 0.5 confirms the monodispersity of nanosized particles (17). Dynamic light scattering (DLS) graph of optimized formulation (F10) was presented in Figure 1A.…”
Section: Preparation and Characterization Of Ea-loaded Slnsmentioning
confidence: 99%